1974
DOI: 10.1530/jrf.0.0400249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraventricular Injections of 6-Hydroxydopamine on Plasma Lh and FSH in Male Rats

Abstract: Summary. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1974
1974
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…LH and testosterone. The hypothesis is consistent with reports that decreased noradrenaline stores suppress the secretion of LH [38,39] and of testos terone [39] in adult male rats. This mechanism may be involved in the feedback control of gonadotropin secre tion, since subcutaneous or intrahypothalamic implanta tions of testosterone lead to a reduced turnover of nor adrenaline in the mediobasal hypothalamus as well as decreased plasma LH levels in castrated rats [40], Activa tion of the central cb-adrenergic system by testosterone has been demonstrated [41], Alternatively, cb-adrenoceptors may be negatively cor related with plasma testosterone levels in an indirect manner involving other neurons.…”
Section: Discussionsupporting
confidence: 93%
“…LH and testosterone. The hypothesis is consistent with reports that decreased noradrenaline stores suppress the secretion of LH [38,39] and of testos terone [39] in adult male rats. This mechanism may be involved in the feedback control of gonadotropin secre tion, since subcutaneous or intrahypothalamic implanta tions of testosterone lead to a reduced turnover of nor adrenaline in the mediobasal hypothalamus as well as decreased plasma LH levels in castrated rats [40], Activa tion of the central cb-adrenergic system by testosterone has been demonstrated [41], Alternatively, cb-adrenoceptors may be negatively cor related with plasma testosterone levels in an indirect manner involving other neurons.…”
Section: Discussionsupporting
confidence: 93%
“…As was recently reported, potentiation of LH responses to NA occurs in 6-OHDA-treated rats (Bacha, Donoso, 1974). This supersensitivity may explain the absence of chronic modifications in LH in animals with central adrenergic lesions (Kitchen, 1974;Kitchen, Ruf, Younglai, 1974;Macdonald, Airaksinen, 1974;Donoso, Bishop, McCann, unpublished). 6-hydroxydopamine may cause, however, some early modifications of gonadotrophin release (Kalnins, Ruf, 1971;Kitchen, 1974;HSkfelt, Fuxe, 1974).…”
Section: Discussionsupporting
confidence: 61%
“…Ojeda and McCann (1973) showed that the rise in plasma LH observed 16 h following orchidectomy was prevented by a-MPT injected 2 h after the castration. A low dose of 6-hydroxydopamine injected into the lateral ventricle caused a functional impairment of catecholaminergic neurons, which resulted in a transient decrease of LH (Kitchen et al, 1974) and testosterone level (Vermes et al, 1977, unpublished) in the peripheral blood. Castration altered the activity of tyrosine-hydroxylase, but not the tryptophan-hydroxylase activity of the hypothalamus in male rats (Kizer et al, 1974).…”
Section: Discussionmentioning
confidence: 99%